Functional characterization of the novel BRAF complex mutation, BRAFV600delinsYM, identified in papillary thyroid carcinoma. Issue 3 (21st July 2012) - Matsuse, Michiko; Mitsutake, Norisato; Tanimura, Susumu; Ogi, Tomoo; Nishihara, Eijun; Hirokawa, Mitsuyoshi; Fuziwara, Cesar S.; Saenko, Vladimir A.; Suzuki, Keiji; Miyauchi, Akira; Yamashita, Shunichi
Abstract An activating mutation in the BRAF gene is the most common genetic alteration in papillary thyroid carcinomas (PTCs). The mutation in PTCs is almost a c.1799T>A transversion, resulting in a p.V600E amino acid substitution (BRAFV600E). Here, we report a novel complex BRAF mutation identified in 4/492 Japanese PTC cases (0.81%). The mutation was comprised of one nucleotide substitution at position 1798, followed by an in‐frame insertion of three nucleotides, c.1798delinsTACA in Exon 15, resulting in p.V600delinsYM. In silico three‐dimensional protein structure prediction implied altered kinase activity of this mutant. In vitro kinase assay and western blotting revealed that this mutation conferred high kinase activity on the BRAF protein, leading to constitutive activation of the MAPK signaling pathway. The mutation also showed high transforming ability in focus formation assay using NIH3T3 cells. The degree of all the functional characteristics was comparable to that of BRAFV600E, and treatment with a BRAF inhibitor Sorafenib was also equally effective in this mutant. These findings suggest that the novel BRAF mutation, BRAFV600delinsYM, is a gain‐of‐function mutation and plays an important role in PTC development.